The sailor's tale - Hopkin, D (Taylor and Francis, 2024)
This article explores the connection between a specific occupational group —long-haul sailors—and a specific genre of oral literature, the sailor’s tale or ‘long yarn’. The style and content of sailors’ tales seems remarkably consistent both over time and space, with ancient, medieval, and modern stories of cannibals, whale islands, magnetic mountains, giant ships (ATU 1960H), among other repeated themes. The sailor’s tale is reputedly both utterly fantastic yet simultaneously expressive of some truth. By investigating the function of stories and storytelling in the challenging conditions aboard ship—how they built reputations, established solidarities, intimated both resistance and accommodation—this paradox will be, if not resolved, at least clarified.